Heat and Mass Transfer Advances in Science and Technology Applications - Iranzo, Alfredo (Heat and Mass Transfer, 2019)
Heat and mass transfer is the core science for many industrial processes as well as technical and scientific devices. Automotive, aerospace, power generation (both by conventional and renewable energies), industrial equipment and rotating machinery, materials and chemical processing, and many other industries are requiring heat and mass transfer processes. Since the early studies in the seventeenth and eighteenth centuries, there has been tremendous technical progress and scientific advances in the knowledge of heat and mass transfer, where modeling and simulation developments are increasingly contributing to the current state of the art. Heat and Mass Transfer - Advances in Science and Technology Applications aims at providing researchers and practitioners with a valuable compendium of significant advances in the field.